Principle Study of a Semi-active Inerter Featuring Magnetorheological Effect - Zhong, Wei-Min; Bai, Xian-Xu; Tang, Chao; Zhu, An-Ding (Frontiers in Materials, 2019)
Inerters are two-terminal mass elements in which the forces applied at the terminals are proportional to relative acceleration between the nodes. The volume and weight of inerters are much smaller than those of any conventional mass element for the same force, which is beneficial for engineering applications. The inerter in mechanical systems corresponds completely to the capacitor in electrical systems, which makes it more convenient to do related investigations based on mechanical-electrical analogies. A semi-active inerter (SAI) featuring a magnetorheological (MR) effect with tunable inertance is proposed, designed, and investigated to enhance the performance of the passive inerters. The proposed SAI consists of a flywheel, a flywheel housing, a ball screw, a connection sleeve, bearings, upper and lower covers, excitation coils, and MR fluid. MR fluid fulfilled in the flywheel housing of the SAI is energized by the excitation coils with applied current, and correspondingly the mechanical characteristics of the SAI are tunable via the applied current. The mathematical model and the mechanical performance of the SAI are established and tested, respectively. The nonlinearity of the experimental results is analyzed and the non-linear model of the SAI is further established. The preliminary principle verification of the continuous adjustment of the equivalent inertance of the SAI is conducted using the non-linear model. Moreover, a compensator is proposed to address the problem of the phase difference between the controllable force and the real output force of the SAI, and continuous inertance adjustment of the SAI with a compensator is realized.